PENGAMBILAN KEPUTUSAN STRATEGIS GIZI DAN KESEHATAN IBU DAN ANAK (KIA) PADA KEPALA DINAS KESEHATAN KABUPATEN/KOTA DI DAERAH ISTIMEWA YOGYAKARTA - Febria Rahmi; Mubasysyir Hasanbasri; Yodi Mahendradhata (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: the high maternal and child mortality andmalnutrition in regency/city in special region of Yogyakartademanded head of health department to take strategicdecisions.Objectives: to describe the strategic decision making by headof health department on the issue of maternal and child healthand nutrition.Methods: qualitative with exploratory study.Results: District health office/city in special region ofYogyakarta have not many strategic decisions to solveproblems on maternal and child health and nutrition. However,the decisions are always be hampered by human resources.Only Gunung Kidul District Health Office which states that therewas no political involvement in decisions by the head of thehealth department.Conclusions: Strategic decisions taken by district healthoffice/city in special region of Yogyakarta such as regulationmayor books Maternal and Child Health, delay the age ofmarriage at the age of the child, WhatsApp group of district levelnutritional recovery home.